Maternal Knowledge and Use of Galactagogues in Andean Communities of Cusco, Peru - Madalena Monteban (Ethnobiology Letters, 2017)
A commonly reported reason for early breastfeeding cessation is inadequate milk production. In response, women across the globe turn to galactagogues – substances used to increase the milk supply. Andean women have traditional knowledge about the medicinal and nutritional properties of plants and animals that are considered good to eat during breastfeeding. This research explores the maintenance and use of galactagogues, and specifically the use of the Andean flicker bird, within the wider framework of breastfeeding and nutrition policies in Peru. To elicit maternal knowledge and use of galactagogues, semi-structured and free-listing interviews were conducted with 33 mothers. Data analysis calculated the frequency and percentage of women reporting each type of galactagogue. In addition, thematic codes and relevant text passages were used in an iterative analytic process to document emerging themes. Identified galactagogues included five plants and six animals. Several galactagogues included protein-rich foods such as lamb meat and the Andean flicker bird. The use of protein-rich galactagogues as solid food is reinforced by public health messages. However, galactagogues in the research communities are usually consumed as soups or drinks, which are less rich in proteins than solid meals. The potential role of liquid galactagogues in the maintenance of appropriate hydration levels during breastfeeding in an environment where safe drinking water is scarce is a new contribution to the existing literature. The results are relevant to the design of maternal and child health policies that comply with intercultural health premises that value and respect the knowledge and practices of Andean Peoples.